2021
DOI: 10.3390/ijerph18020838
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention within the Early Childhood Education and Care Setting: A Systematic Review of Dietary Behavior and Physical Activity Policies and Guidelines in High Income Countries

Abstract: As a strategy for early childhood obesity prevention, a variety of dietary behavior and physical activity policies and guidelines published by leading health agencies and early childhood education and care (ECEC) licensing and accreditation bodies exist. Given the potential diversity in recommendations from these policies, this narrative review sought to synthesize, appraise and describe the various policies and guidelines made by organizational and professional bodies to highlight consistent recommendations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…As such, many governments recommend the implementation of physical activity-promoting practices in this setting. A systematic review conducted by Jackson et al [ 12 ] identified 28 physical activity guidelines for the ECEC sector across high-income countries, spanning over two decades. The recommended physical activity practices contained within these guidelines were summarised into eight broad practices and 44 sub-practices related to promoting physical activity in ECEC settings, providing a comprehensive overview of practice recommendations for the sector.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, many governments recommend the implementation of physical activity-promoting practices in this setting. A systematic review conducted by Jackson et al [ 12 ] identified 28 physical activity guidelines for the ECEC sector across high-income countries, spanning over two decades. The recommended physical activity practices contained within these guidelines were summarised into eight broad practices and 44 sub-practices related to promoting physical activity in ECEC settings, providing a comprehensive overview of practice recommendations for the sector.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for review evidence to be efficiently collated and summarised to provide an overview of the collective findings. An umbrella review of the empirical evidence for physical activity strategies in ECEC mapping to the obesity prevention guidelines as identified by Jackson et al [ 12 ] provides an overview of where there is strong empirical evidence and where there may be gaps, provides opportunities to strengthen recommendations and generates primary evidence to examine this.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different strategies and interventions for PA promotion have been developed and tested in this setting, and a growing number of best practice guidelines and PA recommendations exist for childcare centers ( Finch et al , 2016 ; Wolfenden et al , 2020 ; Jackson et al , 2021 ). However, there is a lack of evidence to inform the successful implementation of evidence-based policies, practices and programs in childcare centers ( Larson et al , 2011 ; Finch et al , 2016 ; Jones et al , 2017 ; Razak et al , 2019 ; Wolfenden et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%